Industry and development global report 1986 (UNIDO ViennaAT, 1986)
Gives an overview of the world industrial economy focussing on recent developments in the North that have impacted on the South. Provides forecasts for 1986 and`87 for 28 manufacturing sectors including textiles. Identifies & discusses short-term problems facing the world economy eg. the debt burden of the South, protectionism and prospects for reflation in the North. Considers long-term implications for industrialization in the South as a result of the rapid technological change in the North. Policy issues and options for the South are also examined. Statistical data for 150 countires are provided at the 28 sector industrial level.
Bibliography: p. 141-145